2015
DOI: 10.1371/journal.pone.0142420
|View full text |Cite
|
Sign up to set email alerts
|

Foot Length, Chest Circumference, and Mid Upper Arm Circumference Are Good Predictors of Low Birth Weight and Prematurity in Ethnic Minority Newborns in Vietnam: A Hospital-Based Observational Study

Abstract: BackgroundThe evaluation of tools to accurately identify low birth weight (LBW) and/or premature newborns in resource-limited countries is a research priority. We explored the use of foot length, chest circumference, and mid-upper arm circumference (MUAC) measured within 24 h as diagnostic tools for identifying newborns who are LBW, premature, or both; and compared measurements taken at birth with those taken at five days of age.Materials and MethodsAn observational study was undertaken in Hoa Binh Province Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
37
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 27 publications
14
37
5
Order By: Relevance
“…For LBW along with preterm, newborn foot length <7.3 cm had 86% sensitivity, 83% specificity, 77% positive predictive value, and 90% negative predictive value in making the diagnosis. 16 Srivastata et al reported very strong positive correlation between newborn foot length and gestational age with correlation coefficient 0.99. 15 Different cut-off points in each study and each country suggests that race or country have a role in determining the cut-off point of the foot length.…”
Section: Discussionmentioning
confidence: 97%
“…For LBW along with preterm, newborn foot length <7.3 cm had 86% sensitivity, 83% specificity, 77% positive predictive value, and 90% negative predictive value in making the diagnosis. 16 Srivastata et al reported very strong positive correlation between newborn foot length and gestational age with correlation coefficient 0.99. 15 Different cut-off points in each study and each country suggests that race or country have a role in determining the cut-off point of the foot length.…”
Section: Discussionmentioning
confidence: 97%
“…Newborn anthropometric studies have been done in a number of settings, assessing correlation between birthweight and a variety of other measures, including foot-length, and have generally shown reasonably good test characteristics for foot-length [2,12,15,16,17,18]. Although most of these studies did not find foot-length to be the best proxy for birthweight, foot-length measurement has seemed more practical for field use than other measures that generally performed better (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Newborn anthropometric studies have been done in a number of settings, assessing correlation between birthweight and a variety of other measures, including foot-length, and have generally shown reasonably good test characteristics for foot-length [2,12,15,16,17,18]. Although most of these studies did not nd foot-length to be the best proxy for birthweight, foot-length measurement has seemed more practical for eld use than other measures that generally performed better (e.g.…”
Section: Discussionmentioning
confidence: 99%